Method and application of coal-based solid waste filling in multi-layer three-dimensional space of coal mining - Ke YANG; Xiang YU; Xiang HE; Xinyuan ZHAO; Juejing FANG; Zhen WEI; Shuxin HE (Meitan kexue jishu)
The resource utilization of coal-based solid waste in mines is the main direction to solve the integrated development of 'safety-technology-economy-environment', and it is also the key to the high-quality green development of the coal industry. Underground filling mining of coal-based solid waste has obvious technical originality advantages in loss reduction mining, solid waste disposal, resource replacement and ecological protection, and has become one of the key paths for resource, scale and green disposal of coal-based solid waste. However, the existing filling mining technology has problems such as limited control effect on overlying strata, lack of linkage effect between multiple filling methods, and low comprehensive utilization rate of coal-based solid waste. Therefore, by summarizing the current situation and existing problems of resource utilization of typical coal-based solid waste in China, the feasibility of coal-based solid waste filling mining is clarified from five dimensions of economy, technology, environment, policy and space. Based on this, the coal-based solid waste filling method in multi-layer three-dimensional space of coal mining was proposed. The connotation and overall idea of this method were systematically expounded, including high-level filling, in-situ filling and low-level filling. Based on the Analytic Hierarchy Process (AHP), an evaluation system of coal-based solid waste filling with 15 evaluation indexes was established. The large-scale application of multi-level three-dimensional space coal based solid waste filling method in coal mining mainly faces 4 key technical challenges, including efficient and accurate preparation of filling materials, pipeline transportation characteristics of filling slurry, evolution law of filling spatial structure and interaction between filling material-space. Focusing on the above key technical challenges, 8 research contents were mainly carried out, including the slurry formation mechanism of coal-based solid waste filling materials, the technical framework of precise preparation of filling materials, the steady-state control mechanism of filling slurry flow field, the key parameters of filling slurry pipeline transportation, the evolution of filling space void structure, the diffusion/bearing characteristics of filling materials, the synergistic mechanism of filling materials-surrounding rock and the multi-field coupling mechanism of filling materials-environment. Based on the mining technology, filling process, and geological conditions of Renjiazhuang Coal Mine in Ningxia Coal Industry and Horxinhe Coal Mine in Shanxi Province, the grouting filling methods in low-level caving zone and high-level separation zone were proposed respectively, which realized the safe and green disposal of coal base solid waste in mining area, effectively controlled the surface subsidence and deformation, and established a good regional demonstration effect. The multi-layer three-dimensional space coal-based solid waste filling method has innovated the new mode of large-scale disposal of coal-based solid waste in underground coal mines, improved the green filling mining technology system, and realized the coordinated control of the whole space of coal mining overburden rock and the leap of solid waste recycling technology, which can promote the fundamental transformation of coal enterprises from “environmental cost type” to “ecological value-added type”.